2019
DOI: 10.1007/s10236-019-01246-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation of second-mode internal solitary waves during winter in the northern South China Sea

Abstract: Key Points: The evolution of an internal tide mode is examined with intermodal coupling.  A generation mechanism of observed mode-2 internal solitary waves during the winter is presented. A mode-1 internal tide can efficiently scatter into mode-2 waves during the winter.Confidential manuscript submitted to replace this text with name of AGU journal Abstract Field measurements of second-mode internal solitary waves (mode-2 ISWs) during the winter on the upper continental slope of the northern South China Sea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Liang et al. (2018) found that mode 2 waves may arise when an initial mode 1 waves propagate into a horizontally varying stratification regime, and Liang & Li (2019) indicated from field observations that a convex internal solitary wave may be generated by a shoaling semidiurnal mode 2 internal tide.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al. (2018) found that mode 2 waves may arise when an initial mode 1 waves propagate into a horizontally varying stratification regime, and Liang & Li (2019) indicated from field observations that a convex internal solitary wave may be generated by a shoaling semidiurnal mode 2 internal tide.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al first reported that Marine measured data of multiple solitary waves within the second baroclinic mode on the continental slope of the northern South China Sea (SCS) [9]. Liang studied the generation mechanism of the field data of the mode -2 ISWs reported by Yang et al, the results shows that the Mode-2I SW is generated by the half-day internal tide (IT) [10]. Magalhaes et al observed five continuous and regularly spaced envelope of Mode-2 ISWs simultaneously in Andaman Sea by using remote sensing technology, results show that Mode-2 ISW may have been overlooked due to their small size in previous remote sensing observations.…”
Section: Figurementioning
confidence: 99%
“…In the Mascarene Ridge and the Andaman Sea, the impact of the ISW beam with the pycnocline is identified as the mechanism responsible for the generation of mode-2 ISWs subsequently developing shorter-scale waves (wave tails with mode-1 structure) (da Silva et al, 2015;Magalhães and da Silva, 2018). Potential mechanisms for the generation of mode-2 waves have been illustrated and they include the instability of shoaling mode-1 waves (Helfrich and Melville, 1986) and their interaction with localized sills (Lamb and Warn-Varnas, 2015), the propagation of mode-1 waves into a horizontally varying stratification regime (Liang et al, 2018), and shoaling mode-2 semi-diurnal internal tides (Liang and Li, 2019). The mode-2 waves receive less attention in the literature compared to mode 1, although some works document mode-2 waves propagating with a mode-1 tail in Knight Inlet, British Columbia (Farmer and Smith, 1980) and/or illustrate their occurrence following mode-1 waves in the South China Sea (Yang et al, 2009;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%